The 3 policemen, or, Young Bottsford of Farbe Island. - Du Bois, William Paene 1916- (Viking Press, 1960)
The ingenuity of ten-year-old Bottsford enables the three policemen of an isolated idyllic isle to catch the thieves who have been stealing the islanders' fish and fishing nets.